Recent activities of the Armenian Virtual Observatory(ArVO) - Mickaelian, A. M.; Mikayelyan, G. A.; Abrahamyan, H. V.; Astsatryan, H. V.; Knyazyan, A. V.
The Astrophysical Virtual Observatories (AVOs) have been created in a number of countries using their available databases and current observing material as a collection of interoperating data archives and software tools to form a research environment for processing complex data-intensive and compute-intensive research workflows. The Armenian Virtual Observatory (ArVO, https://www.aras.am/Arvo/arvo.htm) is a project of the Byurakan Astrophysical Observatory (BAO) aimed at the construction of a modern system for data archiving, extraction, acquisition, reduction, use, and publication. ArVO is based on the Digitized First Byurakan Survey (DFBS, https://www.aras.am/Dfbs/dfbs.html) and is the Armenian contribution to the International Virtual Observatories Alliance (IVOA, https://ivoa.net/). One of the ArVO’s main tasks is to create and utilize a global Spectroscopic Virtual Observatory, which will combine data from DFBS and other low-dispersion spectroscopic databases, as well as provide the first understanding on the nature of any object up to B = 18m. This is important as among all astronomical data, a large spectroscopic database is especially useful for understanding the nature of all observed objects. Hence, ArVO will utilize the DFBS as an appropriate large spectroscopic database. In the frame of ArVO, BAO collaborates with the Institute of Informatics and Automation Problems (IIAP, https://iiap.sci.am/) of the National Academy of Sciences of Armenia to develop software ecosystem for ArVO satisfying the IVOA standards. Besides the DFBS, ArVO provides access to the Digitized Second Byurakan Survey (SBS) database, the Byurakan photographic archive, and BAO 2.6 m and 1 m Schmidt telescopes modern observations.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture